2021
DOI: 10.1007/s42452-021-04188-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and computational study of chromone derivatives with antitumor activity: detailed DFT, QTAIM and docking investigations

Abstract: Theoretical investigations of three pharmaceutically active chromone derivatives, (E)-3-((2,3,5,6-tetrafluorophenyl)hydrazono)methyl)-4H-chromen-4-one (TPC), (E)-3-((2-(2,4,6-trifluorophenyl)hydrazono)methyl)-4H-chromen-4-one (FHM) and(E)-3-((2-(perfluorophenyl)hydrazono)methyl)-4H-chromen-4-one (PFH) are reported. Molecular geometries, vibrational spectra, electronic properties and molecular electrostatic potential were investigated using density functional theory. Quantum theory of atoms in molecules (QTAIM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Density functional theory (DFT) calculations have been performed using the Gaussian computational package to investigate the interionic interaction between [EABu] and CAF. CAM-B3LYP exchange–correlation function in conjunction with the 6-311G ++ (2d, 2p) basis set was employed to perform the geometry optimizations in this work on the Gaussian 09 computational package. Vibrational frequencies of optimized structures were calculated and all the real values of frequency confirm that the optimized geometry corresponds to true minima. The binding energies for isolated ionic liquid were corrected with the basis set superposition error (BSSE) using the Boys Bernardi counterpoise technique .…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations have been performed using the Gaussian computational package to investigate the interionic interaction between [EABu] and CAF. CAM-B3LYP exchange–correlation function in conjunction with the 6-311G ++ (2d, 2p) basis set was employed to perform the geometry optimizations in this work on the Gaussian 09 computational package. Vibrational frequencies of optimized structures were calculated and all the real values of frequency confirm that the optimized geometry corresponds to true minima. The binding energies for isolated ionic liquid were corrected with the basis set superposition error (BSSE) using the Boys Bernardi counterpoise technique .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the quantum theory of atoms in molecules (QTAIM) describes atomic and bond properties based on molecular electron-density distributions [ 3 ]. Both DFT and QTAIM have been used in theoretical investigations on different compounds with anticancer activity [ 4 , 5 , 6 ]. Using these theories, the activity of the chemical compounds may be explained in terms of the predicted chemical reactivity descriptors as well as molecular electrostatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…DFT and the molecular docking studies of Al Sheikh Ali et al [ 4 ] confirmed the results of in vitro experiments on anticancer activity of triazoles derivatives against Caco-2, HCT116, HeLa, and MCF7 cell, indicating the most active among studied compounds. Mary et al [ 5 ] used DFT theory to investigate the molecular geometries, vibrational spectra, electronic properties, and molecular electrostatic potential of pharmaceutically active chromone derivatives. The results of these calculations, together with the QTAIM studies, allowed for the conclusion that the studied compounds possess higher anticancer activity as compared with antitumor standards (5-fuorouracil and azathioprine).…”
Section: Introductionmentioning
confidence: 99%